Characterisation of pharmacokinetics, safety and tolerability in a first‐in‐human study for AZD8154, a novel inhaled selective PI3Kγδ dual inhibitor targeting airway inflammatory disease. Issue 1 (8th August 2021) - Sadiq, Muhammad Waqas; Asimus, Sara; Belvisi, Maria G.; Brailsford, Wayne; Fransson, Rebecca; Fuhr, Rainard; Hagberg, Anette; Hashemi, Mahdi; Jellesmark Jensen, Tina; Jonsson, Julia; Keen, Christina; Körnicke, Thomas; et al.
Abstract : Aims: This 3‐part, randomised, phase 1 first‐in‐human study (NCT03436316) investigated the safety, tolerability and pharmacokinetics (PK) of AZD8154, a dual phosphoinositide 3‐kinase (PI3K) γδ inhibitor developed as a novel inhaled anti‐inflammatory treatment for respiratory disease. Methods: Healthy men, and women of nonchildbearing potential, were enrolled to receive single and multiple ascending inhaled doses of AZD8154 in parts 1 and 3 of the study, respectively, while part 2 characterised the systemic PK after a single intravenous (IV) dose. In part 1, participants received 0.1–7.7 mg AZD8154 in 6 cohorts. In part 2, participants were given 0.15 mg AZD8154 as an IV infusion. In part 3, AZD8154 was given in 3 cohorts of 0.6, 1.8 and 3.1 mg, with a single dose on Day 1 followed by repeated once‐daily doses on Days 4–12. Results: In total, 78 volunteers were randomised. All single inhaled, single IV and multiple inhaled doses were shown to be well tolerated without any safety concerns. A population PK model, using nonlinear mixed‐effect modelling, was developed to describe the PK of AZD8154. The terminal mean half‐life of AZD8154 was 18.0–32.0 hours. The geometric mean of the absolute pulmonary bioavailability of AZD8154 via the inhaled route was 94.1%. Conclusion: AZD8154 demonstrated an acceptable safety profile, with no reports of serious adverse events and no clinically significant drug‐associated safety concerns reported in healthy volunteers. AZD8154 demonstrated prolonged lung retention and a half‐life supporting once‐daily dosing.